2008
DOI: 10.1038/sj.bjp.0707506
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of cannabinoid receptor agonists on regional brain activity using pharmacological MRI

Abstract: Background and purpose: Activation of cannabinoid CB 1 and/or CB 2 receptors mediates analgesic effects across a broad spectrum of preclinical pain models. Selective activation of CB 2 receptors may produce analgesia without the undesirable psychotropic side effects associated with modulation of CB 1 receptors. To address selectivity in vivo, we describe non-invasive, non-ionizing, functional data that distinguish CB 1 from CB 2 receptor neural activity using pharmacological MRI (phMRI) in awake rats. Experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(55 citation statements)
references
References 52 publications
4
50
0
1
Order By: Relevance
“…Furthermore, our study of CB2R signaling indicates that CB2R-related neuroprotection involves the PI3K/Akt pathway. The presence of CB2R in the brain is controversial, particularly with regard to its expression in central neurons (Van Sickle et al, 2005;Chin et al, 2008). Our immunohistochemistry and qPCR data confirmed the absence or low expression of CB2R in the brain under normal conditions, at least for the two structures that we considered-the IO and Pn.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Furthermore, our study of CB2R signaling indicates that CB2R-related neuroprotection involves the PI3K/Akt pathway. The presence of CB2R in the brain is controversial, particularly with regard to its expression in central neurons (Van Sickle et al, 2005;Chin et al, 2008). Our immunohistochemistry and qPCR data confirmed the absence or low expression of CB2R in the brain under normal conditions, at least for the two structures that we considered-the IO and Pn.…”
Section: Discussionsupporting
confidence: 76%
“…Moreover, the expression and function of CB2R in the brain remain controversial. A recent pharmacological MRI study concluded, however, that CB2R is not functionally active in the brain under physiological conditions (Chin et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The uptake of phMRI in research and development has gathered some momentum in recent years as reflected by some elegant, powerful, and thought-provoking work that has been conducted on a variety of targets. Moreover, many of these studies conducted early in the discovery process have afforded enriched translational approaches on disease-relevant central effects of existing and novel experimental therapeutics such as dopamine 3 receptors (D3), 5-hydroxytryptamine 2c, glycine transporter inhibitors, nicotinics, cannabinoid receptor 2/1, and mGluR2/3 (Schwarz et al, 2004(Schwarz et al, , 2007Chin et al, 2008Chin et al, , 2011Gozzi et al, 2008;Beaver et al, 2011;McKie et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This contrasts with brain CB 2 receptors, which pharmacological activation has been questioned in conscious rats (Chin et al, 2008) and, therefore, the presence of any receptor constitutive activity is uncertain. Similarly to δ-opioid receptors (see Fig.…”
Section: Regulation Of Basal Fas/fadd Complex By Cannabinoid Receptorsmentioning
confidence: 99%